Serum Levels of Branched Chain Amino Acids Predict Duration of Cardiovascular Organ Failure in Septic Shock. Issue 1 (July 2021) - Puskarich, Michael A.; McHugh, Cora; Flott, Thomas L.; Karnovsky, Alla; Jones, Alan E.; Stringer, Kathleen A.
ABSTRACT: Background: Sepsis shifts cardiac metabolic fuel preference and this disruption may have implications for cardiovascular function. A greater understanding of the role of metabolism in the development and persistence of cardiovascular failure in sepsis could serve to identify novel pharmacotherapeutic approaches. Methods: Secondary analysis of prospective quantitative proton nuclear magnetic resonance ( 1 H-NMR) metabolomic data from patients enrolled in a phase II randomized control trial of L-carnitine in septic shock. Participants with a sequential organ failure assessment (SOFA) score of > = 5, lactate > = 2, and requiring vasopressor support for at least 4 h were eligible for enrollment. The independent prognostic value of metabolites to predict survival with shock resolution within 48 h and vasopressor free days were assessed. Concentrations of predictive metabolites were compared between participants with and without shock resolution at 48 h. Results: Serum 1 H-NMR metabolomics data from 228 patients were analyzed. Eighty-one (36%) patients met the primary outcome; 33 (14%) died prior to 48 h. The branched chain amino acids (BCAA), valine, leucine, and isoleucine were univariate predictors of the primary outcome after adjusting for multiple hypothesis testing, while valine remained significant after controlling for SOFA score. Similar results were observed when analyzed based on vasopressor free days, and persisted after controlling for confounding variables and excluding non-survivors. BCAA concentrations at 48 h significantly discriminated between those with shock resolution versus persistent shock. Conclusions: Among patients with septic shock, BCAA concentrations independently predict time to shock resolution. This study provides hypothesis generating data into the potential contribution of BCAAs to the pathophysiology of cardiovascular failure in sepsis, opening areas for future investigations. Abstract : Supplemental Digital Content is available in the text